Pengaturan Sudut α Digunakan pada Pengereman motor Induksi 3 Phasa - Hatma Rudito (Jurnal Teknik Mesin Sinergi, 2009)
Braking in induction machine is very important, in this paper discuss problem how to brake machine so that get process good braking and not arouse destruction. In this paper also fundamental topic is dinamic braking use controlled converter 1 phasa and aplication in induction machine 3 phase. Base on data result have doing to get so much litle angle α process braking is quickly and in angle α so much big braking no happen. This braking doing on moment magnetic field in rotor stasionary.